2022
DOI: 10.1088/1361-6501/ac4ed5
|View full text |Cite
|
Sign up to set email alerts
|

A study of the gas interference effects in quadrupole mass spectrometer

Abstract: In most applications, it is significant to understand how the composition and total pressure of the gas affects the sensitivity of mass spectrometer for a specific composition of the gas. This work reported on the interference effects of QMG700 quadrupole mass spectrometer (QMS) with use of the ultrahigh vacuum (UHV) partial pressure standard apparatus and standard leaks. Six combinations for Ar-H2, Ar-He, N2-H2, He-H2, He-N2 and CH4-N2-Ar-He-H2 gas mixtures were selected for the study of the instrument-gas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Step 4: Update the position of each particle x j (n), as shown in Equation (2). According to the four velocities obtained in Step 3, four new positions, denoted as x L j (n + 1), x E j (n + 1), x P j (n + 1), x R j (n + 1), are obtained.…”
Section: Improved Pso Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 4: Update the position of each particle x j (n), as shown in Equation (2). According to the four velocities obtained in Step 3, four new positions, denoted as x L j (n + 1), x E j (n + 1), x P j (n + 1), x R j (n + 1), are obtained.…”
Section: Improved Pso Algorithmmentioning
confidence: 99%
“…The quadrupole mass spectrometer (QMS) is a highly efficient mass spectrometer with excellent sensitivity and selectivity for various analytical applications [ 1 , 2 ], such as clinical diagnosis, the identification and quantification of biomolecules [ 3 ], drug metabolism studies [ 4 ], and environmental monitoring [ 5 ]. With the widespread use of QMS mass spectrometers in recent years, users not only inquire about the higher sensitivity of the instrument, but also pursue the intelligence and automation of the instrument, with analytical experiments performed quickly [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since the factors that cause sensitivity instability of quadrupole mass spectrometers have been reported, 15–19 calibration of such instruments for quantitative analysis of gas mixtures has also been discussed in the literature 20–28 . Regarding hydrogen‐containing mixtures, our literature survey revealed that the interference effect was studied for mixtures of: Ar and H 2 20,21,28,29 ; H 2 , Ne, and Ar 21 ; N 2 and H 2 28,30 ; He and H 2 28 ; Ar and a mixture of H 2 , CO, and CO 2 28 ; a series of H 2 , CO, and CO 2 with a mixture of He, N 2 , and Ar 17 ; and H 2 , O 2 , and CO 2 mixtures 20 . The interference of CO and CO 2 in H 2 has not been addressed frequently.…”
Section: Introductionmentioning
confidence: 98%
“…Ever since the factors that cause sensitivity instability of quadrupole mass spectrometers have been reported, [15][16][17][18][19] calibration of such instruments for quantitative analysis of gas mixtures has also been discussed in the literature. [20][21][22][23][24][25][26][27][28] Regarding hydrogen-containing mixtures, our literature survey revealed that the interference effect was studied for mixtures of: Ar and H 2 20,21,28,29 was used as a second trace gas alongside the same interfering gases, CO and CO 2 . Consequently, QMS sensitivity was also examined for binary deuterium and interfering gas mixtures at different ratios.…”
Section: Introductionmentioning
confidence: 99%